Pertaining Factors on the Audit Quality: Ethical Evidence from Indonesia - Hajanirina Andrianantenaina; Mila Austria Reyes (JAAF (Journal of Applied Accounting and Finance), 2019)
This research attempts to investigate the audit quality based on the pertaining factors including ethical professional behavior, conflict of interest, audit fee that are mediated by religion and cognitive factor. The main issue we tend to discuss relies on the inconsistency of the literature on the audit quality but which ethics represented by the code principles with behavioral constuct prime over the premice. Using survey of 100 auditors from different background (seniority, firm image, and religious aspects); we found that not the ethical behavior matters but the conflict of interest upon the audit quality. Besides, auditor’s fee also becomes a significant parameter of he audit quality. Cognitive factor is necessary for auditor to have best practice on the ethical aspect from the reasoning.